Performance Evaluation of ZigBee in Indoor and Outdoor Environment - Mujahid, Tabassum; Kartinah, Zen (2015)
Wireless Sensor Network (WSN) comprises of many distributed independent tiny sensors that used to monitor statistical data of specific environmental conditions such as temperature, humidity, rain, pressure and many other. WSN use unlicensed 2.4 GHz Industrial, Scientific and Medical (ISM) radio frequency band for data transmission. WSN applications are being used in many industries and civilian areas, for various purposes such as environmental monitoring, habitat monitoring, traffic monitoring, precision agriculture monitoring, security monitoring, facility automation and traceability systems. Deployment of WSN in an outdoor or indoor environment always raised issue of signal loses and signal interference. In WSN, data is transmitted over wireless medium which is easily affected by external aspect such as walls, trees, heavy bushes, multiple signal interference and others. Currently, IEEE standard 802.15.4 MAC protocol and ZigBee are the most famous protocols which are been used in WSN industry. In this paper, we have performed several experiments under various conditions such as indoor, outdoor, co-existence of Bluetooth to observe the ZigBee performance and interference effects. The experiments were performed physically in real environments which showed ZigBee signal degradation under various indoor and outdoor conditions.